PROBLEMS IN OF DEVELOPMENT OF GETTING THE COAL WITH OPENCAST METHOD IN RUSSIA - Kurlenya M.V.; Tanajno A.S.; Cheskidov V.I. (My University, 2001)
Opportunities for development of getting the coal with opencast method in Russian Federation have been considered. Efficiency of further development is largely connected with internal problems in Russian Federation. Part of the problems has been discussed. Structure of location of production capacity has been considered. Intensity of exploiting the coal deposits has been discussed. Quality of the coals has been analyzed. It has been shown that in 1980s, share of coals mined with opencast method was 50 percent. At the present the share is 65 percent. Further growth of the share will be provided and it will be 70-75 percent in the future.